The Influence Of Return on Assets And Return on Equity to Companies Stock Price in the Telecommunication Sector registered in the Indonesia Stock Exchange - Mu'tamaria Mu'tamaria (Journal of World Conference (JWC), 2019)
The purpose of this research is to know the profitability ratios of telecommunication companies listed in Indonesia Stock Exchange period 2014-2017, particularly the influence of profitability ratio to stock price of telecommunication company. This research is conducted on twelve telecommunication companies listed in Indonesia Stock Exchange. The data used are secondary data of financial statements. The analytical technique mobilize multiple linear regression with two dependent variables of ROA and ROE and one free variable of stock price, to test the contribution of variable in influencing the stock price of companies. The results of research on Indonesian telecommunications companies show that the movement of stock prices are not significantly influenced by the value of ROE on Indonesian telecommunications companies. This study found that in the telecommunications company in Indonesia the increased or decreased value of ROA have an influence on the value of the company and the stock price of companies.